Optimizing Network Provisioning through Cooperation - Sharma, Harsha; Thakkar, Parth; Bhagwan, Ranjita; Bharadwaj, Sagar; Padmanabhan, Venkat; Bansal, Yogesh; Kumar, Vijay; Voelbel, Kathleen (NSDI, 2022)
The growth of cloud-scale services has fueled huge growth in inter-data center (DC) Wide-Area Network (WAN) traffic. As a result, cloud providers provision large amounts of WAN bandwidth at very high costs. However, the inter-DC traffic is often dominated by first-party applications, i.e., applications that are owned and operated by the same entity as the cloud provider. This creates a unique opportunity for the applications and the network to cooperate to optimize the provisioning plane, since the demands placed by dominant first-party applications often define the network. Such optimization is distinct from and goes beyond past work focused on the control and data planes (e.g., traffic engineering), in that it help optimize the provisioning of network capacity and consequently helps reduce cost. In this paper, we consider two specific examples of such provisioning plane optimizations: (a) right sizing network capacity based on knowledge of the application’s deadline coupled with network link failure statistics, and (b) realigning application traffic based on knowledge of the underlying link costs. Using data from a tier-1 cloud provider and a large email service, we show that our techniques save more than 30% network capacity, improve link utilization by more than 60% in certain regions and cut cost by 43%.